An Innovative Method for the Control of Legionella Infections in the Hospital Hot Water Systems with a Stabilized Hydrogen Peroxide-Silver Formulation - Shuval, Hillel; Yarom, Rachel; Shenman, Rivka (International Journal of Infection Control, 2009)
Legionella pneumophila contamination of hot water systems are particularly difficult to control due to the optimal growth conditions, protection by biofilms and the fact that chlorine and many other disinfectants are less effective at high temperatures. This paper reports on a 20 month study using an innovative method to control Legionella pneumophila in the closed loop hot water system of a major hospital in Israel, which has suffered a serious out-break of Legionnaires disease in their BMT unit. They had failed to control the Legionella infections by the conventional use of repeated shock treatments with chlorine up to 2000 ppm and by raising the water temperature to 700C. During the period between October 2005 and May 2007 an innovative disinfectant process based on a patented, stabilized, non-toxic, taste free, bactericidal/bacteriostatic, heat resistant formulation of hydrogen peroxide containing a minute amount of oligodynamic silver (commercial name STERIL) was used to effectively disinfect the hot water system and achieve total long term control of Legionella pneumophila. The combined formulation of H2O2 and silver and other metals is some 100 times more powerful as a disinfectant than hydrogen peroxide alone and can provide a long lasting effective disinfectant residual. Our studies show that the formulation's disinfection power increases significantly as water temperature increases which contributes to its effective control of Legionalla bacteria in hot water systems which normally operate at temperatures up to 40-500C. The silver ion deposit on the pipe walls have a bacteriostatic effect. At the end of the 24 month test period it can be stated that the stabilized H2O2-silver formulation effectively controlled Legionella pneumophila in the hospital ward's hot water system for the first time after years of chronic problems and has proved to be a promising and economical option for the long term control of Legionella bacteria in closed loop hot water systems.